A Comparison between Two Different Remineralizing Agents against White Spot Lesions: An In Vitro Study. (19th January 2021) - Alsubhi, Hassan; Gabbani, Mohammad; Alsolami, Abdulsalam; Alotaibi, Mohammed; Abuljadayel, Jameel; Taju, Waleed; Bukhari, Omair
Abstract : Enamel demineralization and white-spot lesions (WSLs) around the orthodontic brackets are common clinical complications after orthodontic fixed appliance therapy. WSLs form mainly due to plaque deposition around the brackets during the orthodontic treatment period. This study was designed to compare and evaluate the efficacy of two different remineralization agents on WSLs, which are "Clinpro 5000 and Colgate Sensitive Pro-Relief". 27 caries-free human premolar teeth were collected after extraction for orthodontic purposes. The crowns were set in acrylic resin, and the entire surfaces were coated with nail varnish apart from an area of 4 × 4 mm on the buccal surface. The surface microhardness (SMH) was measured using the Vickers microhardness testing machine at baseline, after demineralization, and after treatment. Then, the different SMH values were statistically analyzed using mixed-effects linear regression. All samples were immersed in demineralizing solution for ten days to create WSLs, and then the teeth were allocated randomly into one of the three groups: Group 1 (control group-immersed in artificial saliva), Group 2 (treated with Colgate sensitive Pro-Relief toothpaste), and Group 3 (Clinpro 5000 toothpaste). Cycles of treatment were done for 5 minutes every 12 hours for 14 days. The samples were stored in freshly prepared artificial saliva between cycles. The mixed-effects model was used to quantify the effect of different remineralization agents. All statistics were computed using STATA software (version14.1; Stata, College Station, TX). All statistical tests were two-tailed and interpreted at the 0.05 significance level. Both agents improved the surface hardness. Clinpro 5000 improved the surface hardness by 12.7 (P value 0.012), and Colgate Sensitive Pro-Relief improved surface hardness by 18.2 (P value <0.0001), However when both treatments are compared with each other, there was no statistical significance among them. When compared to the control group, both treatments "Clinpro™ 5000 and Colgate Sensitive Pro-Relief" have significantly improved enamel's SMH.